Analisis Respon Spektral dan Ekstraksi Nilai Spektral Terumbu Karang Pada Citra Digital Multispektral Satelit ALOS-AVNIR di Perairan Gugus Pulau Pari, Kepulauan Seribu, Jakarta. - Muhammad Helmi; Agus Hartoko; Herkiki S; Munasik Munasik; S Wouthuyzen (Universitas Diponegoro, 2011)
Abstract Coral reef and other coastal ecosystem map are very important spatial data to provide for many coastal management and planning purposes in Indonesia. Pari Islets of Thousand Islands in the northern coast of Jakarta has great variation on complex coastal ecosystem, such as beach forest, mangrove, coral reefs and seagrass. These rather large shallow and clear water islets could be ideal for satellite image spectral-respond study. The study aimed to asses spectral respond and spectral value of coral reef extraction on ALOS-AVNIR multispectral-satellite image in Pari Islets of Thousand Islands, Jakarta. THSI 4-band multispectral satellite image dated 30 April 2008 (JAXA, 2008) with 10 m spatial resolution. Ground survey was conducted in 85 sampling points between June-July 2009. A set of image processing method including geometric correction, atmospheric calibration (enhanced dark pixel correction), water column correction, Lyzenga transform, Hue Saturation Intensity (HSI) transform, Principle Component 1, scattergram analysis, spectral comparison, was applied for the multispectral image analysis, accompanied by a Line Intercept Transect (LIT) and Manta-taw field survey for the coral reef study. The result showed that coral reef covers area in Pari islets were 249.9 ha (26.5%), seagrass 313.6 ha (33.3%) and shallow water sand 378.9 ha (40.2%). Spectral characteristic of green and red band were much better on differentiating between coral reef and other shallow water substrate compared to the other bands. Visually coral reef identification on HSI transformed image much easier compared to on Lyzenga transformed image. The map accuracy on HSI (88.1%) also higher than Lyzenga (77.3%). Spectral values of coral reef on scattergram were clumped only on specific location and easily differentiated from other shallow water substrates, and so coral reef patch on ALOS-AVNIR satellite image could be extracted directly from the scattergram. Key Word: Spectral respond, Coral reef, ALOS-AVNIR, Multispectral